PERLINDUNGAN HUKUM TERHADAP DRIVER GO-JEK TERKAIT ORDERAN FIKTIF OLEH KONSUMEN GO-JEK DI PEKANBARU - Muhammad Farqi; Firdaus Firdaus; Ulfia Hasanah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
Indonesia’s company introduce the using of motorcycle transportationthrough the app called GO-JEK. GO-JEK is useful app for transportating.Besides, there are misuse of using this app for making a fake booking or so-calledOrderan Fiktif. It makes damnification for the driver of GO-JEK, in case ofmaterial or non-material. This gong to be a big problem for the driver. Thisresearch aims for explain: 1) caused of consumen making the fake booking order,2) the legal protection for the driver because of the case.This research used sociological approach and descriptive method bydescripting how this case occur and find the legal protection. This research took aplace in Pekanbaru city, especially in GO-JEK’s office, and some of sub-disctrictswhose having a driver’s basecamp. The sources use are primary soruce,secondary source, and tertiary source, and the method to collecting the sourcesare interview and library research.By seeing the result of this research, there are two conclusions. 1)economic element caused the case is occur, and by that we already know not onlyconsumen did the fake booking order, also the driver itself. 2) all these violationscause of based on our legal are default, the action againts law, unfair businesscometition, and deception. All the driver could do is calling the customer serviceof GO-JEK or claim to operational office. And for the GO-JEK’s side is recoverdriver’s account and giving a compentation. Researcher suggest, 1) all the driversof GO-JEK should do their business competition as good and not cheat on it, andfor all the consumens should using GO-JEK app wisely. 2) GO-JEK companyshould be doing prevention for minimalizing the fake booking order occur.Keywords : Legal Protection , Driver, Fake Booking Order.